Perio-ortho interdisciplinary approach in the case management of generalised severe periodontitis: Pendekatan interdisipliner perio-orto dalam manajemen kasus generalized severe periodontitis - Ditha Zulistiana; Arni Irawaty Djais (Makassar Dental Journal PDGI Makassar, 2024)
Generalized severe periodontitis is a severe periodontal disease characterized by advance periodontal destruction with clinical attachment loss of 5 mm or more. This condition not only causes tooth mobility but also malocclusion and pathological migration such as protrusion, extrusion, and tooth flaring. For its management, perio-ortho interdisciplinary approach is recommended. This literature aims to review several case reports of patients with GSP who were given comprehensive care through perio-ortho interdisciplinary approach. A total of 35 references were collected through internet-based searches using keywords, seven of which were GSP case reports accompanied by maloclusion and pathological migration in the past eight years analyzed in synthesis table. Such cases are treated by combination of periodontic-orthodontic therapy. The management of GSP combining periodon-tal therapy, antimicrobial treatment, and orthodontic treatment showed improvement in periodontal health status, harmonious and functional occlusion, aesthetic results, and long-term periodontal stability as evidenced by clinical, radiographic, and micro-biological monitoring. It is concluded that the successfull treatment outcome for GSP through perio-ortho interdisciplinary approach is strongly influenced by maintenance of OH, periodic evaluation, use of light continous force, case analysis, and well-defined sequences of treatment.